Anti-Fuzzy Ideal in (m, n)-Near Rings - Fahimeh Mohammadi; Bijan Davvaz (Transactions on Fuzzy Sets and Systems)
In this article, we introduce and discuss the definitions of fuzzy (m, n)-sub near rings, anti-fuzzy (m, n)- sub near rings, fuzzy ideals, and anti-fuzzy ideals in (m, n)-near rings. We establish several fundamental properties and prove key theorems related to these fuzzy structures. Additionally, illustrative examples are provided to enhance understanding and demonstrate the applicability of the concepts.